2011
DOI: 10.1186/1743-422x-8-323
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of efficacy of porcine reproductive respiratory syndrome virus inactivated vaccine based on the viral quantity and inactivation methods

Abstract: BackgroundThere have been many efforts to develop efficient vaccines for the control of porcine reproductive and respiratory syndrome virus (PRRSV). Although inactivated PRRSV vaccines are preferred for their safety, they are weak at inducing humoral immune responses and controlling field PRRSV infection, especially when heterologous viruses are involved.ResultsIn all groups, the sample to positive (S/P) ratio of IDEXX ELISA and the virus neutralization (VN) titer remained negative until challenge. While virem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 25 publications
2
39
0
Order By: Relevance
“…BEI is the most promising of the methods of inactivating PRRSV, which include the following: gamma irradiation, formaldehyde, UV modification, and pH modification. BEI has successfully been used to inactivate PRRSV in previous studies [52,57,58]. In these previous studies, inactivated PRRSV vaccine induced effective immune responses after single intranasal administrations [53,54].…”
Section: Discussionmentioning
confidence: 99%
“…BEI is the most promising of the methods of inactivating PRRSV, which include the following: gamma irradiation, formaldehyde, UV modification, and pH modification. BEI has successfully been used to inactivate PRRSV in previous studies [52,57,58]. In these previous studies, inactivated PRRSV vaccine induced effective immune responses after single intranasal administrations [53,54].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is reasonable to assume that its efficacy will be determined by the homology between the vaccine strain and the strain of the prevalent virus in the farm. In contrast to PRRS MLV vaccine, vaccination with PRRS KV vaccine does not elicit detectable antibodies (Kim et al 2011), but barely elicits cell-mediated immune response to the infecting virus as determined by lymphocyte proliferation and IFNg production in recall response (Bassaganya-Riera et al 2004;Piras et al 2005;Kim et al 2011). These findings lead to the potential application of PRRS KV vaccine as a therapeutic vaccine in PRRSV-positive farms.…”
Section: Journal Of Applied Animal Research 301mentioning
confidence: 89%
“…However, MLV vaccines are of concern, for its immunogenicity, cross-protective efficacy and safety (Labarque et al 2004;Prieto et al 2008;Kimman et al 2009). PRRS KV vaccines, on the other hand, is well known for its safety (Plana-Duran et al 1997;Papatsiros et al 2006Papatsiros et al , 2011, but their capacity to induce a protective immunity against challenge with wild-type virus or heterologous strains has been questioned (Scortti et al 2007;Zuckermann et al 2007;Kim et al 2011). However, field studies reported that the KV vaccines did not induce reproductive failure in vaccinated sows and improved efficiently the reproductive parameters at a farm level (Joisel et al 2001;Papatsiros et al 2006).…”
Section: Introductionmentioning
confidence: 93%
“…It is now generally accepted that inactivated PRRSV vaccines are ineffective for preventing clinical signs and viremia caused by viral challenge [25, 26]. In contrast, MLVs induce better protective immunity than inactivated vaccines [27, 28].…”
Section: Introductionmentioning
confidence: 99%